2014
DOI: 10.1098/rsif.2014.0484
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering changes in spider orb-web topology owing to aerodynamic effects

Abstract: An orb-weaving spider's likelihood of survival is influenced by its ability to retain prey with minimum damage to its web and at the lowest manufacturing cost. This set of requirements has forced the spider silk to evolve towards extreme strength and ductility to a degree that is rare among materials. Previous studies reveal that the performance of the web upon impact may not be based on the mechanical properties of silk alone, aerodynamic drag could play a role in the dissipation of the prey's energy. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 51 publications
0
34
1
Order By: Relevance
“…the spacing between subsequent loops, Figure 1B) of the sticky spiral. Narrow meshes increase the web's prey interception and prey retention capabilities (Rypstra, 1982;de Crespigny, Herberstein & Elgar, 2001;Blackledge & Zevenbergen, 2006) but require higher building costs per web area (Eberhard, 1986), increase the drag of the web (Lin, Edmonds & Vollrath, 1995) and make the web more susceptible to damage in windy conditions (Zaera, Soler & Teus, 2014). Consequently spiders build orb webs with wide meshes when they are exposed to wind (Vollrath et al, 1997;Liao et al, 2009;Wu et al, 2013) but see (Hieber, 1984).…”
Section: Mesh Widthmentioning
confidence: 99%
“…the spacing between subsequent loops, Figure 1B) of the sticky spiral. Narrow meshes increase the web's prey interception and prey retention capabilities (Rypstra, 1982;de Crespigny, Herberstein & Elgar, 2001;Blackledge & Zevenbergen, 2006) but require higher building costs per web area (Eberhard, 1986), increase the drag of the web (Lin, Edmonds & Vollrath, 1995) and make the web more susceptible to damage in windy conditions (Zaera, Soler & Teus, 2014). Consequently spiders build orb webs with wide meshes when they are exposed to wind (Vollrath et al, 1997;Liao et al, 2009;Wu et al, 2013) but see (Hieber, 1984).…”
Section: Mesh Widthmentioning
confidence: 99%
“…Aerodynamic drag forces were introduced following the methodology proposed in Zaera et al [33]. Given the relevance of the stress level in the propagation speed of transverse waves, a pre-stress field was introduced in the webs.…”
Section: Modellingmentioning
confidence: 99%
“…Mechanical modelling provides a valuable methodology to study the structural performance of orb webs in detail and has been deployed to uncover specific aspects of web behaviour under a variety of quasi-static [28][29][30][31][32] and dynamic [33][34][35][36][37] loading conditions. However, the potential of mechanical modelling for the study of wave propagation in webs has been largely unexploited.…”
Section: Introductionmentioning
confidence: 99%
“…Further analysis of the band gap origin is beyond the scope of this letter, since we are focusing on a spider web-inspired structure with different mechanical properties for radial and circular ligaments. 8,9 Another remarkable feature of the band structure in Fig. 2(b) is the smaller number of localized modes compared to the lower bounds are formed by flat curves representing localized motions (Figs.…”
mentioning
confidence: 99%
“…[4][5][6][7] Previous studies have revealed that mechanical performance of spider webs is not only due to the remarkable properties of the silk material, but also to an optimized architecture that is adapted to different functions. 8,9 Structural behaviour of orb spider webs has been extensively analyzed under quasi-static 6,8,10 and dynamic 11,12 loading conditions. However, the spider-web structure has yet to be exploited for the design of phononic structures.…”
mentioning
confidence: 99%